A new oxoaporphine and liriodenine’s anti-neuroblastoma potential from the roots of Polyalthia bullata King - Primus, Phoebe Sussana; Wu, Carol Hsin-Yi; Kao, Chai-Lin; Choo, Yeun-Mun (Penerbit Universiti Kebangsaan Malaysia, 2024)
Polyalthia bullata King’s root yielded a new compound named 5-methylliridine (1) in addition to six previously identified compounds. These known compounds include liriodenine (2), 11-methoxyliriodenine (3), lysicamine (4), onychine (5), 5-hydroxy-6-methoxyonychine (6), and 8-methoxyeupolauridine (7). The structures of compounds 1-7 were determined through spectroscopic analysis. Liriodenine (2) exhibited a remarkable ability to decrease the cell viability of cancerous N2A cells to 22% within a 24 h timeframe, indicating its potential as an anti-neuroblastoma agent. Molecular docking results additionally suggested that oxoaporphines (1-4) have the potential to act as inhibitors of protein kinases. These findings highlight the therapeutic potential of P. bullata constituents in cancer treatment, particularly neuroblastoma, and contribute to understanding its medicinal properties.